Pengaruh Kepemimpinan, Pengembangan Sumber Daya Manusia Dan Beban Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Working Unit Support Desk PT. Sigma Cipta Caraka Tangerang Selatan ) - Darmawan, Reza; Kuncoro, Aris Wahyu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The gap between the targets set by the company and the achievements of the Working Unit Support Desk has resulted in the failure to accomplish several organizational objectives. This condition indicates the need to improve employee performance to ensure that the established targets can be achieved optimally. Therefore, this study aims to analyze the effect of leadership, human resource development, and workload on employee performance at the Working Unit Support Desk of PT. Sigma Cipta Caraka, South Tangerang. This research employs a quantitative approach using a non-probability sampling technique with the saturated sampling method. The population of this study consists of 40 employees, all of whom were included as research samples, resulting in a total of 40 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 22. The results of the study indicate that leadership, human resource development, and workload have a positive and significant effect on employee performance. Therefore, the findings of this research are expected to provide practical contributions for the company in formulating policies aimed at improving employee performance at the Working Unit Support Desk of PT. Sigma Cipta Caraka, South Tangerang.